Radiofrequency Ablation Combined With Transarterial Chemoembolization for Specially Located Small Hepatocellular Carcinoma. (23rd July 2018) - Yuan, Wei; Yang, Min-Jie; Xu, Jiang; Yan, Zhi-Ping; Liu, Rong; Qu, Xu-Dong; Wang, Jian-Hua; Qian, Sheng
Objective: To investigate the safety and efficacy of radiofrequency ablation combined with transarterial chemoembolization in patients with specially located small hepatocellular carcinoma. Materials and Methods: Between March 2014 and March 2017, a total of 26 patients with 26 lesions (10 perivascular, 6 subdiaphragmatic, 5 subcapsular, 5 perivascular, and subdiaphragmatic location; mean diameter 2.12 (0.62) cm), who received radiofrequency ablation–transarterial chemoembolization treatment, were retrospectively analyzed. Local tumor response was assessed by computed tomography/magnetic resonance imaging 1 month after the procedure. Tumor-free survival was also assessed according to the modified Response Evaluation Criteria in Solid Tumors. Complications were evaluated according to the National Cancer Institute's Common Terminology Criteria for Adverse Events (version 4.0). Results: Complete response was achieved in all patients 1 month after the procedure. During a median follow-up duration of 16.76 months (95% confidence interval: 7.78-25.73 months), local tumor recurrence occurred in 2 patients and new intrahepatic lesions developed in 7 patients. The 1-, 2-, and 3-year cumulative local tumor progression rates were 3.84%, 7.69%, and 7.69%, respectively. The median tumor-free survival duration was 21.96 months (95% confidence interval: 17.58-26.34 months). The 1-, 2-, and 3-year tumor-free survival rates were 67.4%, 46.1%, and 39.3%, respectively. Conclusion: The radiofrequency ablation–transarterial chemoembolization combination therapy appears to be safe and effective and might be a treatment option for specially located small hepatocellular carcinoma lesions that have a risk of incomplete ablation or major complications.